Cryopreservation of shoot tips of Rhodiola sachalinensis A. Bor by encapsulation-vitrification and plantlets regeneration - LIU Jian-feng; YAN Xiu-feng; CHENG Yun-qing; LI Xia (浙江大学学报. 农业与生命科学版)
Shoot tips excised from two resources of Rhodiola sachalinensis A. Bor were cryopreserved by encapsulation-vitrification, and effects of sucrose preculture duration, osmoprotection time during encapsulation and exposure time to PVS2 on survival rate of cryopreserved shoot tips of Rhodiola sachalinensis A. Bor were discussed. Excised shoot tips were precultured with increasing sucrose concentrations of 0.3, 0.5, 0.7 and 1.0 mol·L-1 for 1 day respectively, then transferred to 1 mol·L-1 sucrose for 4 days, and precultured shoot tips were encapsulated and simultaneously osmoprotected with a loading solution of 2 mol·L-1 glycerol and 1 mol· L-1 sucrose for 60 min. Osmoprotected and encapsulated shoot tips were dehydrated with a highly concentrated vitrification solution for 180 to 210 min at 0℃ prior to direct immersion in liquid nitrogen for 48 h. After rapid warming in water for 3 min at 40℃, the shoot tips were rinsed with the modified MS medium containing 1 mol· L-1 sucrose for 20 min, and then cultured on the MS medium containing 6-BA 1 mg·L-1 and NAA 0.1 mg· L-1 in dark prior to exposure to the light at 22℃. The best survival rate of encapsulation vitrified shoot tips amounted to nearly 100% and no abnormality was observed.